(untitled) (Journal of the College of Basic Education, 2025)
The current research came with the aim of (revealing stylistic shifts in approaching ethnography visually through films directed by French director Jean Rouch) In four chapters, the first represents an introductory introduction to the research by examining a problem that stems from the following question: (What transformations can be observed in the methods of French director Jean Rouch when he deals with visual ethnography in his cinematic films?) As for the second, it consists of two sections for the theoretical framework, entitled: (Ethnographic Film / Beginnings and Stylistic Transformations, Jean Rouch’s Ethnographic Style), from which the researchers derived the indicators of the research tool. Which was used to analyze the sample, and also included previous studies.The third chapter included the research procedures, represented by the research methodology, the research population, the research sample, the research tool, and the validity of the tool.The fourth chapter included the indicators that the researchers came up with from the theoretical framework and a set of results, the most important of which was that there is an engagement and intermingling of the theoretical ethnographic aspect and its inclusion within the visual and audio structures of the art of cinematic film to produce visual ethnographies dealing with African peoples.simultaneously use natural sound and the general atmosphere of real events while employing the voice of the dramatic character.number of conclusions, recommendations, and some proposals for subsequent studies.